Регламентація громадських організацій Законом «про об’єднання громадян» та Законом «Про громадські організації» (порівняльний аналіз) - Волкова Дарія Євгенівна; Волкова Дарья Евгеньевна; Volkova Dariya (My University, 2012)
The aim of the article was the comparative analysis of the constitutional and legal regulation of NGOs by the Law of June 16, 1992 "On Associations of Citizens" and the Law of March 22, 2012 "On Civil Associations". Comparison of these Laws shows the trend of unification of legislation on NGOs with the civil law. This trend is seen in the thesaurus Law "On Civil Associations", as well as in it’s norms that regulate the creation, the operation and the legalization of NGOs.
Волкова Д. Є. Регламентація громадських організацій Законом «про об’єднання громадян» та Законом «Про громадські організації» (порівняльний аналіз) / Д. Є.Волкова // Юридичний вісник. – 2012. - № 4. - С.177-182.
Keywords: громадські організації; державний контроль; створення громадських організацій; легалізація громадських організацій; общественные организации; государственный контроль; создание общественных организаций; легализация общественных организаций; public organizations; state control; creation of public organizations; legalization of public organizations